Aortic valve replacement for aortic stenosis in France – influence of centers' volumes on TAVR adoption rate and outcomes. (3rd October 2022) - Willner, N A; Nguyen, V; Eltchaninoff, H; Burwash, I G; Michel, M; Durand, E; Gilard, M; Dindorf, C; Iung, B; Cribier, A; Vahanian, A; Chevreul, K; et al.
Abstract: Aims: Over the last decade, transcatheter aortic valve replacement (TAVR) became extensively used, now being the recommended as first line procedure for aortic valve replacement (AVR) in selected patients' populations. It is unknown whether TAVR adoption rate and variability in outcomes is influenced by centers' volume. Methods: From a French administrative hospital-discharge database, we collected all AVR performed in France between 2007 and 2019. Centers were stratified to terciles based on their annual SAVR per year per center during 2007–2009 ("pre TAVR era"). Results: There was 218, 489 AVRs (153, 747 SAVR and 74, 732 TAVR) performed in 46 centers between 2007–2019. Number of total AVR and even more so number of number of TAVR significantly and linearly increased from 2007 to 2019 in all terciles but faster in the high volume tercile (+17, +17 and +31 AVR/center/year in the low, middle and high terciles respectively, P [ANCOVA]<0.001; +11, + 19 and +33 TAVR/center/year in the low, medium and high tercile respectively, P [ANCOVA] <0.00, Figure 1). The age of patients underwent TAVR remained grossly unchanged in all three terciles, however, the Charlson index declined from 2010 to 2019 (from 1.35±1.42 to 0.65±1.04, from 1.21±1.40 to 0.65±1.05 and from 1.53±1.58 to 0.81±1.21, in the low, middle and high terciles, P for trend <0.001, 0.021, and <0.001, respectively). Charlson score in the years 2017–2019, was higher in the high than middle and low terciles (0.87±1.22, 0.76±1.11 and 0.65±1.04, respectively, P<0.0001). The in-hospital mortality rate for TAVR significantly declined from 2010 to 2019 for TAVR in all terciles (from 8.3% to 2.1%, from 7.5% to 2.5% and from 8.2% to 2.1% for low, middle and high TAVR terciles, respectively; p for trend = 0.002, 0.001 and <0.001, respectively, Figure 2). Average mortality in 2017–2019 was similar in all terciles (2.3%, 2.5% and 2.2% for low, middle and high terciles, respectively, P=0.47). After adjusting for age, sex and Charlson score, mortality was higher in the low tercile compared with middle and high terciles (OR 1.15, P<0.001, confidence interval [CI] 1.0–1.2, and OR 1.18, P<0.001, CI 1.1–1.2, respectively). Conclusions: From 2007 to 2019 total AVR linearly increased, mostly due to increase in TAVR, irrespective of centers' volume, but increase rate was higher in high volume centers. A constant decline in patients risk profile, with a striking decrease in mortality rate, was observed in all volume terciles. High-volume centers patients' have higher risk profile, with adjusted mortality slightly lower than medium and low volume centers. Funding Acknowledgement: Type of funding sources: None.